Self-Care of Mental Health Generation Z Ethnic Arek East Java - Yuniarta, Dona Vetrisia; Alfianto, Ahmad Guntur; Kusbandiyah, Jiarti (Jurnal Kesehatan Komunitas Indonesia, 2023)
The lifestyle experienced by Generation Z of the East Java Arek ethnicity causes mental health problems. One of the efforts that can be made to prevent mental health problems is mental health self-care. This study aims to describe the mental health self-care behavior of the Z generation of the East Java Arek ethnicity. The method used is descriptive quantitative research with a survey approach. The population of this research is all Generation Z of East Java Generation ethnicity. The sampling technique used was purposive sampling with 402 respondents Z, ethnic Arek, East Java. The research was conducted in Malang, Sidoarjo, and Surabaya. The measuring tool used is The Mindful Self-Care Scale questionnaire. The data collection technique uses Google Forms, distributed via WhatsApp, WhatsApp groups, Telegram, and social media. Of the results of mental health self-care for generation Z of the Arek ethnicity, 19% carry out self-care, and an average of 82.61 positive behavior the generation Z of the Arek ethnicity in carrying out mental health self-care. Conclusion of mental health self-care Z generation of East Java Arek ethnicity prefers self-care behavior and positive behavior in carrying out mental health self-care.